Quality of life of older adults in Peruvian Social Security during the COVID-19 pandemic - Tenorio-Mucha, Janeth (2021)
Objetive: To evaluate the quality of life of older adults who belong to the Seniors Centers (CAM) of the Social Security during the COVID-19 pandemic. Material and methods: Data were collected through telephone calls to older adults aged 60 years and over in the CAM. Quality of life was assessed with the EQ-5D-3L questionnaire, which considers the dimensions of mobility, self-care, activities of daily living, pain/discomfort and anxiety/depression and an analog scale from 0 to 100. The presence of depression, anxiety, comorbidities and functional status were also measured. A bivariate analysis with nonparametric tests was performed to assess the association between covariates and the quality of life analog scale. In addition, a simple regression analysis was performed using generalized linear models of the Poisson family to evaluate variables associated with the presence of problems in the quality of life dimensions. Results: A total of 99 older adults participated, mostly women (84.9%) and with an average age of 73.1 years, 83.3% had a higher education level and 86.7% lived with their spouse. Older adults with obesity, lung disease, inability to manage their own money, feeling fatigued, and hearing problems reported a lower than average score (<78.9) on the analogous quality of life scale. Osteoarticular diseases and feeling fatigued increase the likelihood of having problems with mobility, performing daily activities, and pain/discomfort. Conclusions: Older adults quality of life is influenced by multiple factors that must be addressed to improve their physical and mental well-being.